Phytochemical constituents in Kithul (Caryota urens) and its medical significance: A mini review - A. D. Theeshya Dulmini; Sarath D. Perera (The Open University of Sri Lanka, 2024)
Kithul (fishtail/toddy palm) tree is scientifically known as Caryota urens. It is an economically and medicinally significant plant native to tropical Asia. This plant consists of major phytochemical constituents including polyphenols (e.g., caffeoylquinic acids, caffeoylshikimic acids, etc.), flavonoids (e.g., quercetin, kaempferol, eriocitrin, etc.), amino acids, fatty acids, phytosterols and sugars. The phloem sap of Kithul tree, collected from the tapped inflorescence is called sweet toddy and it is mainly used to prepare an alcoholic beverage, commonly known as Kithul toddy. Phloem sap is also used to produce treacle and jaggary. Kithul toddy is obtained by fermenting the sap while treacle is made by heating the fresh sap. In the pith of the tree, the sap is stored as starch, and this is later transformed into flour. Phytochemicals present in Kithul roots, leaves, bark, seeds, flowers, and sap exhibit medicinal properties such as anti-diabetic, anticancer, antioxidant, antimicrobial, anti-inflammatory, libidoenhancing ability, etc. Hence, the parts of Kithul tree are used as traditional and Ayurvedic medicine to treat many different conditions such as rheumatic swelling, snake bite poisoning, tooth ailments, anemia, jaundice, etc. The main scope of this article is to review major phytochemical constituents in Kithul plant and how its medicinal properties benefit the world.